Diagenetic, thermal and provenance histories of the Permian lower Ecca Group based on two newly drilled boreholes in the western and eastern main Karoo Basin, South Africa - Geel, Claire (Department of Geological Sciences, 2021)
Fine-grained sedimentary rocks of the Lower Permian lower Ecca Group in the Main Karoo Basin (MKB) in southern Africa have been identified to form a possible unconventional hydrocarbon reservoir, the gas potential of which is still relatively unknown. The lower Ecca Group is comprised of flysch-like successions of the Prince Albert, Whitehill and Collingham formations, which were impacted by diagenesis as well as contact and regional and metamorphism. Studies of fine-grained sedimentary rocks are notoriously complex as mechanical breakdown and diagenesis result in mineralogical changes and loss of source rock information. Therefore, a variety of analytical techniques are required for their thorough investigation. In this study, we analyse Permian rocks from two boreholes (KZF-1 and KWV-1) that were drilled ~ 830 km apart in the western and eastern MKB, respectively, and compare their composition, thermal maturity and petrophysical characteristics to better assess the hydrocarbon potential of the lower Ecca Group. In addition, whole rock geochemistry is used to reconstruct the palaeo-environment and provenance settings. Lastly, we investigate the influence of shale composition, porosity, well pressure and temperatures on their geomechanical properties such as compressive strength and elastic moduli. Sedimentary rocks in both boreholes were affected by burial and regional metamorphism (linked to orogenic events), but the sedimentary rocks in BH KWV-1 were also altered by contact metamorphism due to dolerite intrusions in the Early Jurassic. Major mineralogical differences between the boreholes include: 1) Fesilicate (greenalite); carbonates (rhodochrosite and dolomite) and Mn nodules (birnessite) being found only in BH KZF-1; and 2) metamorphic minerals such as garnet, cordierite, staurolite being found only in BH KWV-1. The results show that these rocks are over mature as evidenced by the low quantity of free hydrocarbons (S1 peak; 0.02–0.06 mg/g) and potential to release hydrocarbons (S2 peak; 0.06– 0.14 mg/g) and low hydrogen index (HI) values (2.40–167 mg HC/g TOC) from Rock Eval pyrolysis accompanied with high vitrinite/bitumen reflectance (BH KZF-1 is VRo= 4 and BH KWV-1 is BRo= 5). The total organic carbon (TOC) content is the highest in the Whitehill Formation in both boreholes (BH KZF-1: 5.17 wt%; BH KWV-1: 4.87 wt%). Burial diagenesis significantly reduced interparticle porosity and most of the measurable porosity comes from intraparticle nano-pores confined to organic matter v and dolomite. Meso- and macro-porosity are limited to phyllosilicates, pyrite framboids and microfractures. The Chemical Index of Alteration (CIA) is highest for the Prince Albert Formation (72– 78) as the palaeo-environment changed from an ice-house to a green-house, postglacial period in southern Gondwana. Enrichment of trace elements in BH KZF-1 and BH KWV-1 are in order: Mn > Ba > Zn > Co > Cu > V > Rb > Cr > Ni; and for BH KWV-1: Mo > Ba > Cu > Zn > Mn > V > Co > Cr > Rb > Ni. Geochemical proxies used in determining levels of anoxia were: V/Cr, V(V+Ni), Ni/Co and Fe-S-TOC plots. Salinity was deduced using Rb/K ratios and with identification of potential benthic foraminifera and minerals such as apatite, birnessite and phosphate nodules, which are assumed to be syn-sedimentary in origin. Overall, the geochemical results indicate that the depositional conditions fluctuated with respect to anoxia, salinity levels, and that while the sedimentation rates were low and the bio-productivity level was high, at least episodically. Provenance was investigated using Discriminant Function Diagrams, Principle Component Analysis Results (PCA), Zr/Ti ratios and the Index of Compositional Variability (ICV). Results indicate that the Prince Albert and Whitehill formations in the western MKB comprises sediment that was mostly sourced from the Cambrian to Late Carboniferous Cape Granite Suite, Cape Supergroup, the Dwyka Group and possibly the Precambrian Kango Group (Saldania Belt) and/or the Namaqua-Natal Belt. The Prince Albert and Whitehill formations in the eastern MKB have a mafic signature, indicating that these sediments may have been derived from the PermoCarboniferous Dwyka Group, Precambrian Kaapvaal Craton, Natal Belt (Tugela Terrane), Natal Group and the Pan-African Mozambique and Maud Belts. The mudstone and wackes in the Collingham Formation were mostly sourced from the quartz-arenites and granites that were most likely associated with the Cape Fold Belt, the orogen immediately adjacent to and largely coeval with the MKB. Geomechanical results from BH KZF-1 show that the lower Ecca Group has a high proportion (~ 50–70 vol%) of mechanically strong minerals (e.g., quartz, feldspar, pyrite), ~ 30–50 vol% weak minerals (e.g., clay, organic matter) and up to ~ 0–50 vol%, highly variable, intermediate components (e.g., carbonates). Constant strain rate deformation experiments (T ≤ 100 °C; p ≤ 50 MPa) and compressional tests performed perpendicular and parallel to bedding show that the Prince Albert Formation is the strongest and most brittle followed by the Collingham Formation and then the Whitehill Formation. Triaxial compressive strength as well as static Young's vi moduli increased with increasing hard minerals and decreased with increasing mechanically weak minerals and porosity. On comparison with European and American shales, the shales in the lower Ecca Group are geomechanically stronger and more brittle, and thus may allow for fracture propagation without rock breakdown under pressure. The lower Ecca Group varies from the western to the eastern MKB in mineralogy, thermal maturity, palaeo-depositional environment and provenance. These observations directly challenge the previous assumptions that these black shales were deposited under predominantly anoxic conditions. Indeed, during deposition, the levels of anoxia appear to have been inconsistent across the MKB and were likely dependent on the changing primary bio-productivity levels, sedimentation rates and basin morphology. Neither borehole contained significant gas, likely due to degasification by dolerite intrusions in the Early Jurassic and structural deformation during syn- and post-Karoo times. In summary, this study quantitatively confirms that the lower Ecca Group has the potential to be an easily frackable, unconventional shale gas reservoir. However, this study also attests to the compositional and geomechanical complexity of these Karoo rocks, and this inevitably translates to a gas potential that is expected to vary significantly across the basin.